Advances of Tumorigenesis, Diagnosis at Early Stage, and Cellular Immunotherapy in Gastrointestinal Malignancies - Zhu, Haipeng; Liu, Xiaojun (Frontiers in Oncology, 2021)
Globally, in 2018, 4.8 million new patients have a diagnosis of gastrointestinal (GI) cancers while 3.4 million people died of such disorders. GI malignancies are tightly relevant to 26% of the world-wide cancer incidence and occupies 35% of all cancer-associated deaths. In this article, we principally investigated molecular and cellular mechanisms of tumorigenesis in 5 major GI cancers occurring at esophagus, stomach, liver, pancreas, and colorectal region that illustrate high morbidity in Eastern and Western countries. Moreover, through this investigation, we not only emphasize importance of the tumor microenvironment in forming and developing malignant tumors, but also identify remarkable progression of M2PK, miRNAs, ctDNAs, circRNAs and CTCs in early detection of GI cancers, as well as systematically analyze the advantages and barriers of applying cellular immunotherapy, cancer vaccine therapy and oncolytic virotherapy in treatment of GI malignant disorders.